2007
DOI: 10.1038/nm1557
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of AdipoR1 and AdipoR2 causes abrogation of adiponectin binding and metabolic actions

Abstract: Adiponectin plays a central role as an antidiabetic and antiatherogenic adipokine. AdipoR1 and AdipoR2 serve as receptors for adiponectin in vitro, and their reduction in obesity seems to be correlated with reduced adiponectin sensitivity. Here we show that adenovirus-mediated expression of AdipoR1 and R2 in the liver of Lepr(-/-) mice increased AMP-activated protein kinase (AMPK) activation and peroxisome proliferator-activated receptor (PPAR)-alpha signaling pathways, respectively. Activation of AMPK reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
1,027
8
17

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,223 publications
(1,124 citation statements)
references
References 40 publications
41
1,027
8
17
Order By: Relevance
“…16 We confirmed that AdipoR1 or R2 knockout mice showed abrogation of AdipoR1 or R2 protein, respectively. In wild-type mice, adiponectin binds specifically to hepatocytes, whereas targeted disruption of both AdipoR1 and R2 completely abrogated adiponectin-specific binding to hepatocytes.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…16 We confirmed that AdipoR1 or R2 knockout mice showed abrogation of AdipoR1 or R2 protein, respectively. In wild-type mice, adiponectin binds specifically to hepatocytes, whereas targeted disruption of both AdipoR1 and R2 completely abrogated adiponectin-specific binding to hepatocytes.…”
Section: Introductionsupporting
confidence: 68%
“…These data indicated that AdipoR1 and R2 serve as the major AdipoRs in vivo. 16 AdipoR1 knockout mice and double knockout mice exhibited insulin resistance and impaired glucose tolerance, whereas AdipoR2 knockout mice exhibited insulin resistance without glucose intolerance. These data indicated that AdipoR1 and R2 play physiologically important roles in the regulation of insulin sensitivity and glucose metabolism in vivo.…”
Section: Introductionmentioning
confidence: 95%
“…36 Fatty acids are critical determinants of insulin resistance and we investigated the expression of CPT-1, which contributes to the utilization of energy and fatty-acid metabolism by increasing mitochondrial lipid oxidation. 11 CPT-1 expression was elevated in rats from ULs, regardless of their diet after weaning, suggesting that there may be some long-term effects of early undernourishment on fatty-acid oxidation and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Yamauchi et al. 2007, 2002). Fesus and colleagues were the first group to show a vasodilation to adiponectin, demonstrating a robust effect of adiponectin at healthy human serum concentrations (3  ÎŒ g/mL) on wire mounted rat or mouse aorta or mouse mesenteric arteries preconstricted with serotonin (Fesus et al.…”
Section: Introductionmentioning
confidence: 99%